2016
DOI: 10.3389/fcell.2016.00087
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Inorganic Arsenic Is Associated with Increased Mitochondrial DNA Copy Number and Longer Telomere Length in Peripheral Blood

Abstract: Background: Exposure to inorganic arsenic (iAs) through drinking water causes cancer. Alterations in mitochondrial DNA copy number (mtDNAcn) and telomere length in blood have been associated with cancer risk. We elucidated if arsenic exposure alters mtDNAcn and telomere length in individuals with different arsenic metabolizing capacity.Methods: We studied two groups in the Salta province, Argentina, one in the Puna area of the Andes (N = 264, 89% females) and one in Chaco (N = 169, 75% females). We assessed ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 55 publications
2
11
1
Order By: Relevance
“…In the present study, arsenic concentrations in both maternal blood, urine and placenta were positively associated with placental rTL. We have previously found positive associations between arsenic exposure and telomere length in blood of adults in the same Andean area [44, 45]. Similar findings were reported for adults in Bangladesh [46] and India [47] and among adolescents in Nepal [26].…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, arsenic concentrations in both maternal blood, urine and placenta were positively associated with placental rTL. We have previously found positive associations between arsenic exposure and telomere length in blood of adults in the same Andean area [44, 45]. Similar findings were reported for adults in Bangladesh [46] and India [47] and among adolescents in Nepal [26].…”
Section: Discussionsupporting
confidence: 78%
“…In particular, the creatinine-corrected urine arsenic, cadmium and tungsten median concentrations in the SHS (1989-1991) were 8.9, 1.0 and 0.11 μg/g, respectively, and in the SHFS (2001-2004) were 4.3, 0.44 and 0.10 μg/g, respectively, while in NHANES data from 2004-2005 the median levels were 5.6, 0.17, 0.07 μg/g for ΣAs, Cd and W, respectively. Some epidemiologic studies have explored the association between arsenic exposure and telomere length, generally reporting positive associations (17)(18)(19)(20)(21)(22), i.e, increased arsenic exposure associated with longer telomeres. However, most of those studies are small and conducted in populations exposed to high levels of arsenic in drinking-water.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on the relationship between TL and arsenic have been conducted among populations affected by high arsenic exposure. In particular, small studies from Nepal (17), Argentina (18,19), Bangladesh (20), and India (21) suggested a positive association between arsenic and TL, while a study from Italy found a borderline inverse association (22). Cadmium exposure, however, has been consistently associated with shorter telomeres in Nepal (17) and NHANES 1999NHANES -2002.…”
Section: Introductionmentioning
confidence: 99%
“…As described previously, SYBR Green-based real-time quantitative PCR (7900HT, Applied Biosystems, Foster City, CA, USA) was used to determine relative mtDNAcn and TL [ 32 ]. Master mixes for mtDNA and hemoglobin beta ( HBB ) gene runs were prepared with KAPA SYBR FAST qPCR Kit Master Mix (2X) ABI Prism (Kapa Biosystems, Woburn, MA, USA) and corresponding primers (0.20 μM for each primer) [ 33 , 34 ]. Master mixes for telomere runs were prepared with telomere primers (0.45 μM for each primer) [ 35 ], 1 × PCR Buffer (Thermo Fisher Scientific, Carlsbad, CA, USA), 1.75 mM MgCl 2 , 0.8 mM dNTPs, 0.3 mM SybrGreen (Thermo Fisher Scientific), 1 × Rox (Thermo Fisher Scientific), and 0.5 U Taq Platina (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%